The corporate instigation of community-based organizations: analysis of two oil and gas companies in India - Siddiky, Shakera (2016)
There is increasing evidence to suggest that Corporate Community Involvement (CCI) has gone beyond philanthropy towards more innovative approaches in addressing complex social problems. One example is particularly evident in developing countries where corporations organize the local community in their operational areas into community-based organizations (CBOs), such as self-help groups, and enable them to tackle social problems by themselves. In this thesis, I explore this emerging CCI mode, termed Corporate Instigation of Community-Based Organizations (CICBO), by focusing on the contexts in which such engagement is conceptualized, the process through which it is put into practice and the outcomes of such engagement.